2008
DOI: 10.1021/jp7119944
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Deposition of C60 on a Hydrogen-Bonded Supramolecular Network

Abstract: An electrospray technique has been successfully used to deposit C 60 onto a hydrogen-bonded supramolecular template held in an ultrahigh vacuum environment. Characterization of the surface by in situ scanning tunneling microscopy shows the size-selective trapping of C 60 dimers and heptamers within a 3,4,9,10-perylene tetracarboxylic diimide (PTCDI)/melamine network. We demonstrate that ultrahigh vacuum electrospray deposition (UHV-ESD), where energetic molecules impact onto a substrate, is compatible with sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…32,33,34 Current developments of adapted electrospray and soft-landing techniques now permit the transfer of essentially any molecule or salt from solution to UHV. 35,36,37,38,39 d) The spatial resolution of UHV-STM (and now NC-AFM) is much higher than in solution, allowing precise characterization of sub-atomic details and conformations and precise measurements of interatomic distances. STM manipulation of single atoms and molecules is now a routine and precise technique that allows perturbation of the observed system to evaluate its stability and to displace molecules.…”
Section: Vacuum-solid Versus Liquid-solid Interfacesmentioning
confidence: 99%
“…32,33,34 Current developments of adapted electrospray and soft-landing techniques now permit the transfer of essentially any molecule or salt from solution to UHV. 35,36,37,38,39 d) The spatial resolution of UHV-STM (and now NC-AFM) is much higher than in solution, allowing precise characterization of sub-atomic details and conformations and precise measurements of interatomic distances. STM manipulation of single atoms and molecules is now a routine and precise technique that allows perturbation of the observed system to evaluate its stability and to displace molecules.…”
Section: Vacuum-solid Versus Liquid-solid Interfacesmentioning
confidence: 99%
“…Some previous work has considered the co-assembly of C 60 and p-conjugated oligomers (e.g., oligothiophenes [51][52][53] and sexiphenyl [54][55][56]) on single crystal metal surfaces, and demonstrated that H-bond directed p-conjugated assembly can dictate the solid state arrangement of C 60 on surfaces [57][58][59][60][61][62][63][64][65][66][67]. Resulting C 60 overlayer structures have included dimerization at high coverage on anthracene carboxylic acid layers on Ag(1 1 1) [59,64,65], and dimeric and hexameric clusters residing within various supramolecular assemblies of perylene tetracarboxylic diimide and melamine on Au(1 1 1) [61][62][63]66]. In the former case, the organic structure corresponds to a complete coverage and the molecules themselves template the overlying C 60 structures.…”
Section: Assembly On a Mebqph Monolayermentioning
confidence: 99%
“…The adsorbed Mn 12 (acetate) 16 may be induced to form structures with different order when deposited on a surface on which a hydrogenbonded nanoporous network has been prepared. We have previously shown that nanoporous supramolecular templates can be formed on the Au(111) surface by combining the organic building blocks PTCDI (3,4,9,10-perylene tetracarboxylic diimide) and melamine (1,3,5-triazine-2,4,6-triamine) 33,47,48 .…”
Section: Stm Of Adsorbed Mn 12 (Acetate)mentioning
confidence: 99%
“…The UHV-ESD experimental setup has been described in detail previously 33,34 . To summarize, a solution containing the molecules to be deposited is passed through a stainless steel emitter held at ~2 kV at a typical flow rate of 1 µl min − 1 .…”
Section: Uhv-esdmentioning
confidence: 99%
See 1 more Smart Citation